2014
DOI: 10.3390/mi5040943
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Laser Beam Shaping Optics Based on Their Ablation Geometry of Thin Films

Abstract: Thin film ablation with pulsed nanosecond lasers can benefit from the use of beam shaping optics to transform the Gaussian beam profile with a circular footprint into a Top-Hat beam profile with a rectangular footprint. In general, the quality of the transformed beam profile depends strongly on the beam alignment of the entire laser system. In particular, the adjustment of the beam shaping element is of upmost importance. For an appropriate alignment of the beam shaper, it is generally necessary to observe the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 8 publications
1
37
0
Order By: Relevance
“…The measured intensity profiles matched the simulated ones well (Figures S2 and S3, Supporting Information). Shaped laser beams can also be characterized by the ablation geometry of thin films . The ablation results corresponded well to our simulation results (Figure b).…”
supporting
confidence: 87%
“…The measured intensity profiles matched the simulated ones well (Figures S2 and S3, Supporting Information). Shaped laser beams can also be characterized by the ablation geometry of thin films . The ablation results corresponded well to our simulation results (Figure b).…”
supporting
confidence: 87%
“…Their research has shown a significant improvement in holes' quality, especially in drilling brass plates compared to a conventional Gaussian profile. In another investigation, a square top-hat beam was used to scribe 150 nm thin films of indium tin oxide using both refractive and diffractive beam shapers [42,43]. The uniform energy profile of the square top-hat beam allowed for a smaller pulse overlap to be used and this led to nine-fold increase in the scribing speed compared to Gaussian beam processing while achieving a similar quality.…”
Section: Application Of Top-hat Beams In Laser Micro-machiningmentioning
confidence: 99%
“…[1][2][3] Especially, when lasers are used to ablate materials or illuminate photomasks in manufacturing processes, it is often desirable to have a uniform intensity distribution over the cross-section of the beam. [4][5][6] Extensive efforts have been made to develop essential design and fabrication techniques to meet this need. [7,8] In general, designing a beam-shaping system needs to consider two steps, i.e., a phase profile φ(x, y) needed to yield some target intensity profile and an optical element that can generate the desired phase profile.…”
Section: Doi: 101002/adom201800961mentioning
confidence: 99%